1992
DOI: 10.1002/ajp.1350260111
|View full text |Cite
|
Sign up to set email alerts
|

Nonsocial behavior of captive infant gorillas

Abstract: Frequencies of eight nonsocial behaviors (object contact, environmental exploration, mouthing, self-directed behavior, display behavior, solitary behavior, rest, and locomotion) were obtained for 20 infant lowland gorillas (Gorilla gorilla gorilla) between 14 and 36 months of age. They lived in 13 groups in 10 zoological collections. Approximately 12 hours of one-zero data were collected on each animal. Behavioral data were analyzed with regard to the following independent variables: rearing history of the foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Self-directed behaviors were infrequent and showed no significant change over time. In contrast, high frequencies of self-directed behavior in socially deprived (Fossey, 1979) and hand-reared (Gold, 1992) gorilla infants have been reported, indicating that the infant in this study was engaging in developmentally appropriate behaviors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Self-directed behaviors were infrequent and showed no significant change over time. In contrast, high frequencies of self-directed behavior in socially deprived (Fossey, 1979) and hand-reared (Gold, 1992) gorilla infants have been reported, indicating that the infant in this study was engaging in developmentally appropriate behaviors.…”
Section: Discussioncontrasting
confidence: 67%
“…Overall, the total affiliative social behavior of the infant significantly increased over time, and he was observed engaging in only affiliative social behaviors. In contrast to the infant in this study, human-reared gorilla infants have been reported to exhibit frequent, unprovoked aggressive display behaviors (Gold, 1992) as have infants deprived of maternal care (Meder, 1989).…”
Section: Discussionmentioning
confidence: 93%
“…(Rogers & Davenport, 1969;Lemmon, 1971). By the second year of life hand-reared gorillas have been found to exhibit more selfdirected behaviour (including selfgrooming), display behaviour and regurgitation and reingestion, and they do not rest as much or take as much interest in exploring their environment (Gold, 1992). However, Lemmon (1971) suggests that 'good' hand-rearing may provide an adequate substitution for conspecific socialization and that early sexual experience is not a necessary prerequisite for future competency in this area.…”
mentioning
confidence: 99%
“…The two factors that appear to influence good maternal behaviour most are to be mother-reared (MMR) (Beck & Power, 1988;Gold, 1992) and to grow up in a social breeding group where maternal behaviour by conspecifics can be observed readily (OBS) (Kirchshofer, 1970;Bingham & Hahn, 1974;Meder, 1989;Hannah & Brotman, 1990;Schmidt, 1993). These both have significant results in most analyses and are even more significant when analysing breeding success (BS:BF), which is an accurate means of assessing survival.…”
Section: The Developing Zoo Worldmentioning
confidence: 99%